Political Participation and Electoral System - Albán Peralta, Walter (2006)
This paper analyzes the changes that have occurred in the Peruvian legal system since 1992, focusing on the electoral sphere. In this context, it offers a reflection on the interruption of the constitutional regime that led to the replacement of the 1979 Constitution by the current Magna Carta of 1993. In this regard, it discusses three relevant issues that arose from the changes in the electoral system or in the constitution itself. These include political representation in Congress, political parties, and electoral institutions. The author points out the absence of a unified system of norms and the lack of state organization in electoral matters, and also highlights how reforms have been implemented mainly in response to new political situations and specific events, without taking into account the impact or consequences of such decisions.